2012
DOI: 10.1289/ehp.1103996
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Early Childhood Exposure to Tetrachloroethylene and Adult Vision

Abstract: Background: Tetrachloroethylene (PCE; or perchloroethylene) has been implicated in visual impairments among adults with occupational and environmental exposures as well as children born to women with occupational exposure during pregnancy.Objectives: Using a population-based retrospective cohort study, we examined the association between prenatal and early childhood exposure to PCE-contaminated drinking water on Cape Cod, Massachusetts, and deficits in adult color vision and contrast sensitivity.Methods: We es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The cohort was originally designed to investigate associations of prenatal exposure to PCE (tetrachloroethylene or perchloroethylene), a VL/AC pipe leachate and drinking water contaminant, with multiple health outcomes [14,15,16]. Study participants additionally reported detailed information on their childhood fish intake.…”
Section: Methodsmentioning
confidence: 99%
“…The cohort was originally designed to investigate associations of prenatal exposure to PCE (tetrachloroethylene or perchloroethylene), a VL/AC pipe leachate and drinking water contaminant, with multiple health outcomes [14,15,16]. Study participants additionally reported detailed information on their childhood fish intake.…”
Section: Methodsmentioning
confidence: 99%
“…The 63 participants with early life exposure whose vision was examined also had evidence of long-term subclinical visual dysfunction 16 . Participants exposed to high PCE levels exhibited lower contrast sensitivity at intermediate and high spatial frequencies compared to unexposed participants.…”
Section: Resultsmentioning
confidence: 99%
“…Eligible subjects who completed the survey were also invited to participate in a clinical study comprised of neuropsychological tests to evaluate visuospatial abilities, attention and executive function, short-term memory, motor skills, academic achievement, omnibus intelligence and mood; vision exams to assess color discrimination and contrast sensitivity; and magnetic resonance imaging (MRI) to measure white and gray matter volumes and white matter hypointensities 1618 . Prior studies among adults suggested that these outcomes might be affected by early life exposure to solvents 2125 .…”
Section: Summary Of Methods Used In the Cape Cod Health Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The parent study that generated these data was undertaken to examine a wide range of neurotoxic effects following prenatal and early postnatal exposure to PCE contaminated drinking water. Outcomes that were examined included risky behaviors (Aschengrau, et al 2011); mental illness (Aschengrau, et al 2012); clinical and behavioral problems and learning disabilities based on questionnaire data (Janulewicz, et al 2008); and subtle functional changes assessed with neuropsychological (Janulewicz, et al 2012) and vision tests (Getz, et al 2012); overt structural brain changes using MRIs. The current paper focuses only on the structural MRI results.…”
Section: Introductionmentioning
confidence: 99%